Shrooms - Sean McGinley; Sean McGinley; Joe Phelan; Lindsey Haun; Anna Tikhonova; Don Wycherley (Magnolia USA, 2007)
When five American college students arrive in Ireland to go on camping trip with their old college buddy Jake they are in high spirits. Jake has promised them the trip of a lifetime because he claims Ireland has the best magic mushrooms in the world. It sounded like it would be great fun. Now that they are tripping things don t seem so funny. BLUTO one of the gang is missing. TARA thinks he s dead because she feels she has seen his death before but nobody believes her they think she is just out of it. They re out of it too. That was the whole point of coming here but there is something out there something watching them something that will kill them if they don t get out of the forest and get help.
Languages : English, Turkish Subtitle : Turkish
Keywords: Horror